Discovery of Tenuipalponychus (Acari: Tetranychidae) inMalaysia and description of a new species - Othman, Yusof; Zhang, Zhi-Qiang (Zootaxa, 2003)
The genus Tenuipalponychus Channabasavanna & Lakkundi (Acari: Tetranychidae) is recorded for the first time from Malaysia. Tenuipalponychus rosae Yusof & Zhang sp. nov. is described from females collected on Rosa chinensis from Cameron Highlands, Pahang, Malaysia. A key to world species of Tenuipalponychus is provided.